Nonintrusive Installation of the TMR Busbar DC Current Sensor. (8th February 2021) - Xu, X. P.; Liu, T. Z.; Zhu, M.; Wang, J. G.
Abstract : In recent years, new energy vehicles, photovoltaic power stations, communication base stations, energy storage systems, and other power electronic systems have developed rapidly. The development of these systems has the trend of continuously increasing the power density per unit area, reducing the system volume, and continuously increasing using the busbars. More and more new current sensors will be used in these systems and play a key role. Traditional current sensor cannot meet the development trend of power electronic systems due to their large size and high cost. In this paper, a new small coreless tunnel junction magnetoresistance (TMR) busbar dc current sensor adopted differential scheme which improves the sensor's anti-interference ability that is designed. The current sensor adopts an open-closed structure for easy nonintrusive installation. Four TMRs which adopted differential structure are placed on the edges of the busbar. The peak current measurement range is ±600 A, the rated current measurement range is ±300 A, and the supply voltage is 5 V.